Relação entre carga mental de trabalho e infecção hospitalar em UTI - Silva , Ravenna Leite da (2018)
Introduction: In a hospital environment, the mental effort of nurses can be generated by the need to meet the patient's demands, the interaction with patients or family members, associated with the most intense emotional aspects of life. Therefore, it can be assumed that this environment has an effect on the workload. Several studies focused on the analysis of the nursing workload were concentrated with instruments focused on the evaluation of the physical workload (intensity and volume of work). These instruments, in turn, seem insufficient for the measurement of the workload, which must be comprehensive and dynamic, and there is a need for literature that considers the mental load before the activities / work situations that promote its increase. There are still few studies that address the mental workload of nurses in ICU settings. Objective: to verify the relationship between the mental workload of nurses and the hospital infection in an Intensive Care Unit. Method: Participants in the sample were nurses who performed their work activities during the day shift. Data collection took place in two periods: December 2017 with a total of 16 participants and April 2018 with 14 participants. The following research instruments were used: (1) socioeconomic questionnaires; (2) NASA-TLX for analyzing the mental workload of nurses; (3) Nursing Work Index Brazilian version to evaluate organizational aspects of the sector, and finally, (4) consult the database of the Hospital Infection Control Service to collect data on levels of hospital infection. The Spearman correlation test was applied to verify the association between the mental work load of the participants and the hospital infection levels, α = 0.05. Results: Nurses' mental workload was high, with a NASA-TLX weighted average of 66.38 (SD ± 15.0). Correlations were found between the levels of hospital infection in the sector and the mental load of the nurses (r = 0.654, p <0.01), with emphasis on urinary tract infection associated with the delayed bladder catheter (r = 0.546, p <0 , 01) and pneumonia associated with mechanical ventilation (r = 0.563, p <0.01). The ICU presented a favorable environment to nursing practices with means lower than 2.5, according to the Nursing Work Index Brazilian version. Conclusion: The mental workload of the nurses was associated with the infection levels of the intensive care sector, mainly urinary tract infection associated with the use of a bladder catheter and ventilator-associated pneumonia.